On a novel lapping method for RB-SiC ceramic materials by integration of fixed-abrasive with even-sprayed micro-droplets - Yang Yu; Xuanping Wang; Xiaoguang Guo; Hang Gao (Journal of Materials Research and Technology)
Reaction-bonded silicon carbide (RB-SiC) ceramic is a promising material for space telescopes due to its high strength, lightweight, and low thermal expansion rate. However, its high hardness and brittleness bring difficulties to efficient processing with high quality. In this study, a novel fixed-abrasive spray suspension lapping (FSSL) process is proposed to achieve high-quality and efficient lapping of large-aperture RB-SiC mirrors, which can be integrated with computer controlled optical surfacing (CCOS) technology. With the effects of load force, spray pressure, and grit size on material removal characteristics and surface quality investigated, the results show that the material removal profile avoids center concentration and becomes uniform by virtue of spray suspensions, leading to improvement of surface quality. With observation of surface microstructure, the ductile-regime removal mechanism will result in a high-quality surface, and the minimum roughness Sa 13.5 nm is obtained. Finally, based on the rough surface contact theory, the material removal mechanism is discussed by comparing the average penetration depth of the abrasive and the critical depth of ductile-brittle transition.